Development of Promotion and Customer Management Programs at Jempol Food - Prayitno, Agung; Nuvriasari, Audita (Asian Journal of Community Services, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) in the Special Region of Yogyakarta Province has experienced rapid growth in recent years, where in 2022 there were 342,924 business units and in 2023 it increased to 344,757 business units.CV Prasodjo is one of the MSMEs engaged in the processing of basic food ingredients or snacks with a trademark called Jempol Food. These MSMEs have experienced quite rapid development but are still experiencing a number of problems in their business operations, especially in the field of marketing. The programs implemented are the development of online promotional content, personal selling optimization, the preparation of customer databases, the development of customer loyalty programs and helping production process activities. The purpose of this program is to improve Jempol Food's business performance through training activities and marketing program development.